DISSEMINATED INTERSTITIAL GRANULOMA ANNULARE - Barbará, Eduarda Faísca (2014)
We report a clinicopathological case of a 62-year-old patient with a diagnosis of interstitial granuloma annulare, characterized by grouped papules without central atrophy, distributed in the lower limbs, buttocks and back. Histopathology was essential for diagnostic conclusion, since the initial assessment, the disease was not among the clinical hypotheses.